2019
DOI: 10.1111/cns.13125
|View full text |Cite
|
Sign up to set email alerts
|

Continuous infusion of an agonist of the tumor necrosis factor receptor 2 in the spinal cord improves recovery after traumatic contusive injury

Abstract: Summary Aim The activation of the TNFR2 receptor is beneficial in several pathologies of the central nervous system, and this study examines whether it can ameliorate the recovery process following spinal cord injury. Methods EHD2‐sc‐mTNF R2 , an agonist specific for TNFR2, was used to treat neurons exposed to high levels of glutamate in vitro. In vivo, it was infused directly to the spinal cord via osmotic pumps immediately after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…In this line, we showed that coadministration of glutamate and EHD2-scTNF R2 into the magnocellular nucleus basalis of mice protected cholinergic neurons and their cortical projections from excitotoxic cell death induced by glutamate and reverted the injury-associated memory impairment testes by a passive avoidance paradigm (Dong et al, 2016). Similar, using a mouse model of contusive injury, Gerald et al showed that EHD2sc-mTNF R2 -mediated activation of TNFR2 in the spinal cord improved locomotion and cortical neural activity (Gerald et al, 2019). Due to the important role of TNFR2 for neuroprotection, we went on to study the neuroprotective role of TNFR2 in models of CNP.…”
Section: Selective Activation Of Tnfr2 Using Agonistic Tnf Muteins Anmentioning
confidence: 64%
“…In this line, we showed that coadministration of glutamate and EHD2-scTNF R2 into the magnocellular nucleus basalis of mice protected cholinergic neurons and their cortical projections from excitotoxic cell death induced by glutamate and reverted the injury-associated memory impairment testes by a passive avoidance paradigm (Dong et al, 2016). Similar, using a mouse model of contusive injury, Gerald et al showed that EHD2sc-mTNF R2 -mediated activation of TNFR2 in the spinal cord improved locomotion and cortical neural activity (Gerald et al, 2019). Due to the important role of TNFR2 for neuroprotection, we went on to study the neuroprotective role of TNFR2 in models of CNP.…”
Section: Selective Activation Of Tnfr2 Using Agonistic Tnf Muteins Anmentioning
confidence: 64%
“…The protective effect of zinc on astrocytes inhibits demyelination damage 47 . Zinc directly or indirectly affects the expression of related proteins, such as the regulation of the tumor necrosis factor receptor 2 48 . The changes in some central nervous system cells and related protein factors in the acute phase of spinal cord injury can effectively affect the pathological changes of spinal cord injury and promote wound healing.…”
Section: Discussionmentioning
confidence: 99%
“… 47 Zinc directly or indirectly affects the expression of related proteins, such as the regulation of the tumor necrosis factor receptor 2. 48 The changes in some central nervous system cells and related protein factors in the acute phase of spinal cord injury can effectively affect the pathological changes of spinal cord injury and promote wound healing. Anti‐inflammatory environment, the more anti‐inflammatory and antioxidant effects of zinc require further experiments to verify these conjectures and perfect the mechanism of action of zinc.…”
Section: Discussionmentioning
confidence: 99%
“…TBI can lead to a significant increase in patient mortality and poor long‐term prognosis, leaving many survivors with long‐term disabilities 3‐6 . SCI triggers a robust neuroinflammatory response and disrupts essential neuroimmune communication causing serious deficits in sensorimotor functions 7‐10 . The incidence rate of SCI varies from regions to countries and increases when human activities are increasingly greater 11 .…”
Section: Introductionmentioning
confidence: 99%